Study on Pressure-Bearing Patterns of Gel Plugging Agents in Multi-Scale Fractures - Shuanghu Si; Yifei Liu; Yinghui Jiang; Chenwei Zou; Ning Yang; Dongfang Lv; Xizhuo Miao; Caili Dai (Gels)
In fractured reservoirs, fractures serve as both water channeling and oil flow channels. Because of the impact of bottom water coning, the water channeling phenomenon becomes more problematic in the middle and late stages of reservoir development. Furthermore, residual oil is limited to small-scale fractures. In multi-scale fractures, the conventional pressure-bearing pattern of plugging agents is ambiguous. This results in low oil recovery, low sweep efficiency from water flooding, and low plugging agent application efficiency. Until now, the pressure-bearing patterns related to gel strength in multi-scale fractures have not been clear. In this paper, the gelation performances of temperature-resistant gel (TRG) samples with different elastic moduli were investigated. The elastic modulus of the TRG was normalized by the elastic modulus (G′) and viscosity modulus (G″). Subsequently, we carried out research on the bottom water pressure patterns of TRGs. This study revealed the pressure-bearing patterns of the TRGs under multi-scale fractures. A corresponding influence pattern chart was established, and the optimal surface function was fitted using the MATLAB nonlinear surface data fitting method. Finally, an application experiment for the characteristic chart was carried out. The plugging rate was evaluated based on the permeability reduction and pressure differential across the core samples before and after gel injection. Subsequently, a TRG with certain elastic moduli before and after plugging the core fracture node was selected from the chart. The elastic modulus of the TRG at the injection node prior to plugging was 14.29 Pa. The elastic modulus of the TRG at the injection node after plugging was 19.42 Pa. The experimental results showed that the TRG with an elastic modulus of 19.42 Pa effectively plugged the fractures and remained stable for over 90 days under a pressure differential of 53 KPa, resulting in a 58.7% improvement in oil recovery compared with water flooding. However, it was difficult for the TRG with an elastic modulus of 14.29 Pa to plug fractures efficiently, and it only enhanced the oil recovery by 15.2%. The primary aim of this work was to establish a quantitative and normalized evaluation method for temperature-resistant gels (TRGs) used in fractured reservoirs. By introducing a classification system based on the elastic modulus (G′) and correlating it with the fracture scale and plugging performance, this study bridges the gap between laboratory gel evaluations and field applications. The results provide practical design criteria and contribute to improving the efficiency and adaptability of gel plugging strategies under harsh reservoir conditions.